Pengaruh Kompetensi, Independensi, Etika Dan Skeptisme Profesional Terhadap Kualitas Audit (Studi Kasus Kantor Inspektorat Eks Karisidenan Surakarta) - Silmiyati, Mira (2016)
Intention of this research is to analyses and test influence of interest, independency, ethics, and professional skeptic have an effect on to quality of audit in Inspectorate ex of region of Surakarta covering; of Surakarta City, Sub-Province of Sukoharjo, Sub-Province of Klaten, Sub-Province of Boyolali, Sub-Province of Sragen, Sub-Province of Karanganyar, and Sub-Province of Wonogiri. This research use quantitative method by using obtained primary data of questioner. Population in this research is entire Inspectorate government officer ex of region. Amount of sample in this research counted 107 auditors in. Method gathering of sample use technique of purposive sampling. Used analyzer cover validity test and test of reliabilities, test normality, test multikoliniarities, test heteroskedastisities, test doubled linear regression, test of F, coefficient test of determines R, and test of t. Pursuant to result of data analysis can be concluded that competence variable have an effect on to quality of audit, because tcount (4,281) > ttable (1,984) with level of significant t equal to 0,000 < (0,05). While independency variable have an effect on to quality of audit, because tcount (3,340) > ttable (1,984) with level of significant t equal to 0,001 < (0,05). Then at ethics variable have an effect on to quality of audit, because tcount (4,525) > ttable (1,984) with level of significant t equal to 0,000 < (0,05). Professional skeptic therefore have an effect on to quality of audit, because tcount (-2,371) > ttable (1,984) with level of significant t equal to 0,020 < (0,05). And so it is with test by simultan (in concern) show result of statistical test of distribution of Fcount > Ftable that is 19,184 > 2,46 with value probability smaller than level of significance research 5%, that is equal to 0,000. Adjusted R2 equal to its 0,407 meaning of interest, independency, ethics, and professional skeptic can explain variability's ofis quality of audit equal to 40,7%.